2016
DOI: 10.5296/ijsw.v3i1.8750
|View full text |Cite
|
Sign up to set email alerts
|

Human Trafficking in Peru: Stakeholder Perceptions

Abstract: Peru has been found to be a country of destination, origin, and transit of men, women, and children subjected to forced labor and sex trafficking. Peruvian news highlights growing trends in labor and sex trafficking, but it is widely recognized that there is a paucity of rigorous data on the subject.This study interviewed stakeholders involved in prevention, intervention, and support of victims of human trafficking in Peru. The research team surveyed thirty human trafficking organizations throughout Peru. Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Studies with service providers as participants have often stressed CCSE survivors' mental health service needs (Clawson, Salomon, & Grace, 2008;Countryman-Roswurm, & Shaffer, 2015;Greenbaum & Crawford-Jakubiak, 2015;Hardy, Compton, & McPhatter, 2013;Hossain, Zimmerman, Abas, Light, & Watts, 2010;Levine & Schumacher, 2017;Oram et al, 2015;Rafferty, 2018). However, many CCSE victims are trapped in the sex trade due to poverty and other vulnerability factors (e.g., childhood experiences of sexual abuse, limited education, and homelessness) linked to basic human needs (Clawson, Salomon, & Grace, 2008;Dank et al, 2015;Greenbaum & Crawford-Jakubiak, 2015;Laser-Maira, Huey, Castro, Ehrlich, & Nicotera, 2018;Laser-Maira, Huey, Castro, & Ehrlich,, 2016;Naramore, Bright, Epps, & Hardt, 2017;Roe-Sepowitz, 2012;Steiner et al, 2018). In studies of survivors as participants, food, housing and job opportunities were stated as their primary needs (Estes & Weiner, 2001;Curtis, Terry, Dank, Dombrowski, & Khan, 2008;Hounmenou & Her, 2018;Laser-Maira, Huey, Castro, Ehrlich, & Nicotera, 2018;Maney et al, 2011;Swaner et al, 2016).…”
Section: Physiological Needs: Biological and Genetic Factors Impactinmentioning
confidence: 99%
“…Studies with service providers as participants have often stressed CCSE survivors' mental health service needs (Clawson, Salomon, & Grace, 2008;Countryman-Roswurm, & Shaffer, 2015;Greenbaum & Crawford-Jakubiak, 2015;Hardy, Compton, & McPhatter, 2013;Hossain, Zimmerman, Abas, Light, & Watts, 2010;Levine & Schumacher, 2017;Oram et al, 2015;Rafferty, 2018). However, many CCSE victims are trapped in the sex trade due to poverty and other vulnerability factors (e.g., childhood experiences of sexual abuse, limited education, and homelessness) linked to basic human needs (Clawson, Salomon, & Grace, 2008;Dank et al, 2015;Greenbaum & Crawford-Jakubiak, 2015;Laser-Maira, Huey, Castro, Ehrlich, & Nicotera, 2018;Laser-Maira, Huey, Castro, & Ehrlich,, 2016;Naramore, Bright, Epps, & Hardt, 2017;Roe-Sepowitz, 2012;Steiner et al, 2018). In studies of survivors as participants, food, housing and job opportunities were stated as their primary needs (Estes & Weiner, 2001;Curtis, Terry, Dank, Dombrowski, & Khan, 2008;Hounmenou & Her, 2018;Laser-Maira, Huey, Castro, Ehrlich, & Nicotera, 2018;Maney et al, 2011;Swaner et al, 2016).…”
Section: Physiological Needs: Biological and Genetic Factors Impactinmentioning
confidence: 99%
“…This study was the first of its kind and emphasized the dire need for more investigations into the growing labor and sex trafficking operations within isolated, often illegal, mining communities throughout Peru . A current empirical research study of human trafficking in Peru found that approximately 80% of victims of human trafficking were female and 80% were children or youth (Laser-Maira, Huey, Castro & Ehrlich, 2016). Additionally, approximately 4 out of 10 were often trafficked for the purpose of labor and 8 out of 10 were trafficked for the purpose of sex (Laser-Maira, Huey, Castro & Ehrlich, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Those that were trafficked for sex work often ended up as street prostitutes, brothel prostitutes, involved in sex tourism or pornography (Laser-Maira, Huey, Castro & Ehrlich, 2016). Survivors who were exploited for sex trafficking usually worked one to two years with some over five years (LaserMaira, Huey, Castro & Ehrlich, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Its persistence is proof of this criminality's ability not only to survive, but to thrive, fueled by increasing levels of poverty, migration, and the vulnerability of humans (Hepburn & Simon, 2013). Modern slavery is composed of the sale, transfer, and receipt of human beings, known today as human trafficking or trafficking in persons (TIP), and entraps people through infinitely varied forms of force, fraud, and/or coercion (Laser-Maira, Huey, Castro, & Ehrlich, 2016;Laser-Maira, Huey, Castro, Ehrlich, & Nicotera, 2018). According to the United Nations (UN), TIP generates $32 billion to $36 billion in profit annually, third only to drug and arms trafficking (UN, 2014), and that market is rapidly growing.…”
mentioning
confidence: 99%